(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the incidence, clinical course, and modern treatment methods of food allergies in children. Information is provided on the etiology, diagnosis, and innovative approaches used in the treatment of food allergies. Measures to prevent this disease are also discussed. Studies examine the immunological basis of food allergies, mechanisms of action on the body, and stages of disease development. In addition, the most common allergenic products among children, their pathophysiological effects, and the course of allergies in different age groups are discussed. The article also presents the latest scientific achievements in the diagnosis and treatment of food allergies based on international and local scientific sources.